Musical Theatre as an Object of Transnational Political Exchange: The Case of Isaac Dunayevsky’s Operettas in Czechoslovakia - Frank, Vojtěch (Historical Studies on Central Europe, 2022)
The paper focuses on the ways Czech-language theatres in Czechoslovakia were dealing with the obligatory presence of Soviet operetta titles in their repertoire, dating from about 1950 to 1989. The reform of Czech musical theatre began right after World War II. In search of the right, nationalized form of operetta, Czech theatre organs soon understood that the example must be drawn from the hegemonic Soviet culture. In the Soviet discourse, mainly Isaac Dunayevsky’s operettas were considered masterpieces, and Czech theatre politicians were soon paying their attention to them. After some initial difficulties in obtaining material for the operettas, Dunayevsky’s pieces entered Czech theatre and stayed on the repertoire to the beginning of the 1960s. After the Warsaw Pact Invasion in 1968, Soviet operettas re-entered the theatres’ repertoire; however, their reception and staging circumstances were much more complicated. The paper focuses on the main tendencies in staging Dunayevsky’s operettas in Czechoslovakia, the political and cultural background of productions, and the various ways of presenting it in Czech society and culture. The cultural and historical microprocesses analysed may then throw light on a wider range of historical and cultural phenomena, including cultural transfers and relations between Czechoslovakia and the Soviet Union, the discrepancies between the official and unofficial discourse, as well as the role of popular musical theatre in a socialist society.